Scientometric diagnosis of the use of remote sensing images in Landscape Ecology studies - doi: 10.4025/actascibiolsci.v35i1.8444 - Sarragiotto, Mariana Cristina; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2012)
This work analyzed the implementation of images from the remote sensors ASTER, CBERS, IKONOS, LANDSAT, MODIS, NOAA, QUICKBIRD and SPOT in Brazilian and international Landscape Ecology studies, developed between 1991 and July 2009. The study analyzed works published in article form using the ISI Web of Knowledge website, and theses and dissertations from the “Thesis Database” at CAPES (Coordenação de Aperfeiçoamento de Pessoal de Ensino Superior). A total of 124 Brazilian and 144 international published works were examined, analyzing 11 and six parameters, respectively. It was observed that the images from sensors MODIS (53%) and LANDSAT (32%) are employed more frequently in international research studies, whereas in Brazil there is preference for products from LANDSAT (65%) and SPOT (11%). The interval with the highest scientific output occurred between 1999 and 2009 (95%) in Brazil and from 1997 to 2009 (93%) internationally, while 2008 was the most significant year for both assessments, accounting for 19 and 18% of published works, respectively. The intense use of satellite imagery in Landscape Ecology studies observed in the last decade indicates there will be an increase in this technology in landscape analysis in coming years.